One Friday in April : a story of suicide and survival - Antrim, Donald (W.W. Norton & Company, 2021)
"A searing and brave memoir that offers a new understanding of suicide as a distinct mental illness. As the sun lowered in the sky one Friday afternoon in April 2006, acclaimed author Donald Antrim found himself on the roof of his Brooklyn apartment building, afraid for his life. In this moving memoir, Antrim vividly recounts what led him to the roof and what happened after he came back down: two hospitalizations, weeks of fruitless clinical trials, the terror of submitting to ECT-and the saving call from David Foster Wallace that convinced him to try it-as well as years of fitful recovery and setback. One Friday in April reframes suicide-whether in thought or action-as an illness in its own right, a unique consequence of trauma and personal isolation, rather than the choice of a depressed person. A necessary companion to William Styron's classic Darkness Visible, this profound, insightful work sheds light on the tragedy and mystery of suicide, offering solace that may save lives"--